Neuroprotective effects of hypothermia on synaptic actin cytoskeletal changes induced by perinatal asphyxia - Muñiz, Javier Andrés (2014)
Cerebral hypoxia–ischemia damages synaptic proteins, resulting in cytoskeletal alterations, protein aggregation and neuronal death. In the previous works, we have shown neuronal and synaptic changes in rat neostriatum subjected to hypoxia that leads to ubi-protein accumulation. Recently, we also showed that, changes in F-actin organization could be related to early alterations induced by hypoxia in the Central Nervous System. However, little is known about effective treatment to diminish the damage. The main aim of this work is to study the effects of birth hypothermia on the actin cytoskeleton of neostriatal post-synaptic densities (PSD) in 60 days olds rats by immunohistochemistry, photooxidation and western blot. We used 2 different protocols of hypothermia: (a) intrahypoxic hypothermia at 15 °C and (b) post-hypoxia hypothermia at 32 °C. Consistent with previous data at 30 days, staining with phalloidin–Alexa488 followed by confocal microscopy analysis showed an increase of F-actin fluorescent staining in the neostriatum of hypoxic animals. Correlative photooxidation electron microscopy confirmed these observations showing an increment in the number of mushroom-shaped F-actin staining spines in neostriatal excitatory synapses in rats subjected to hypoxia. In addition, western blot revealed β-actin increase in PSDs in hypoxic animals. The optic relative density measurement showed a significant difference between controls and hypoxic animals. When hypoxia was induced under hypothermic conditions, the changes observed in actin cytoskeleton were blocked. Post-hypoxic hypothermia showed similar answer but actin cytoskeleton modifications were not totally reverted as we observed at 15 °C. These data suggest that the decrease of the body temperature decreases the actin modifications in dendritic spines preventing the neuronal death.